2022
DOI: 10.1177/00914150221106095
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mindset Predicts Cognitive Gains in an Older Adult Multi-Skill Learning Intervention

Abstract: Growth mindset (belief in the malleability of intelligence) is a unique predictor of young learners’ increased motivation and learning, and may have broader implications for cognitive functioning. Its role in learning in older adulthood is unclear. As part of a larger longitudinal study, we examined growth mindset and cognitive functioning in older adults engaged in a 3-month multi-skill learning intervention that included growth mindset discussions. Before, during, and after the intervention, participants rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…Our training program, which was individually tailored to students' learning needs with the goal of mastering fundamental number knowledge, effectively improved both numerical skills 29 and growth mindset in children. Similar to our behavioral findings, a previous study with older adults also found increased growth mindset following cognitive intervention, which enhanced learning in parallel 14 . Our findings suggest that a positive learning experience focused on mastery of learning materials may facilitate children to endorse growth mindset by fostering beliefs that their abilities can be improved through effort and reducing attribution of their success or failure to fixed traits 5,30 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our training program, which was individually tailored to students' learning needs with the goal of mastering fundamental number knowledge, effectively improved both numerical skills 29 and growth mindset in children. Similar to our behavioral findings, a previous study with older adults also found increased growth mindset following cognitive intervention, which enhanced learning in parallel 14 . Our findings suggest that a positive learning experience focused on mastery of learning materials may facilitate children to endorse growth mindset by fostering beliefs that their abilities can be improved through effort and reducing attribution of their success or failure to fixed traits 5,30 .…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, the stronger positive impact of growth mindset on math skills observed in the training, compared to control, group indicates that the influence of growth mindset on achievement is strengthened by cognitive training. These findings converge on related literature pointing to a positive correlation between growth mindset and performance gains in response to training in other domains such as working memory and cognitive control [14][15][16] . Our findings suggest that a training program that focused on mastery of contents can positively influence learning in children.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, prior research presents varied outcomes regarding age-associated differences in the relationship of growth mindset with intrinsic work motivation. Some studies suggest a more notable association among younger employees [ 75 , 80 ], while others find no discernible difference [ 81 , 82 ]. Furthermore, limited research has ventured into this domain within the context of Chinese academic institutions.…”
Section: Literature Reviewmentioning
confidence: 99%